Question
(5) \( \begin{array}{l}\text { solve the metric measurement equation. } \\ 75.24 \mathrm{cg}-3 \mathrm{dg}=\square \mathrm{dg}\end{array} \)
Ask by Gross Summers. in the United States
Feb 03,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
\[
75.24\,\text{cg} - 3\,\text{dg} = 4.524\,\text{dg}
\]
Solution
To solve the equation:
\[
75.24\,\text{cg} - 3\,\text{dg} = \square\,\text{dg}
\]
we need to convert all measurements to the same unit. Let's convert everything to **decigrams (dg)**.
### Understanding Metric Prefixes:
- **Centigram (cg)**: \(1\,\text{cg} = 0.01\,\text{g}\)
- **Decigram (dg)**: \(1\,\text{dg} = 0.1\,\text{g}\)
From this, we can deduce:
- \(1\,\text{dg} = 10\,\text{cg}\)
- Therefore, \(1\,\text{cg} = 0.1\,\text{dg}\)
### Conversion Steps:
1. **Convert 75.24 cg to dg:**
\[
75.24\,\text{cg} \times 0.1\,\frac{\text{dg}}{\text{cg}} = 7.524\,\text{dg}
\]
2. **Subtract 3 dg:**
\[
7.524\,\text{dg} - 3\,\text{dg} = 4.524\,\text{dg}
\]
### Final Answer:
\[
75.24\,\text{cg} - 3\,\text{dg} = 4.524\,\text{dg}
\]
**Rounded (if necessary):**
\[
4.524\,\text{dg} \approx 4.52\,\text{dg}
\]
Reviewed and approved by the UpStudy tutoring team
Like
error msg
Explain
Simplify this solution
Mind Expander
To solve the equation \( 75.24 \mathrm{cg}-3 \mathrm{dg}=\square \mathrm{dg} \), first, we need to convert \( 75.24 \mathrm{cg} \) to decigrams (dg). Since \( 1 \mathrm{cg} = 0.1 \mathrm{dg} \), we have: \[ 75.24 \mathrm{cg} = 75.24 \times 0.1 \mathrm{dg} = 7.524 \mathrm{dg}. \] Now we can rewrite the equation: \[ 7.524 \mathrm{dg} - 3 \mathrm{dg} = \square \mathrm{dg}. \] Calculating this gives: \[ 7.524 \mathrm{dg} - 3 \mathrm{dg} = 4.524 \mathrm{dg}. \] Thus, the answer is: \( \square = 4.524 \mathrm{dg}. \)